Valuing Bioactive Lipids from Green, Red and Brown Macroalgae from Aquaculture, to Foster Functionality and Biotechnological Applications - Diana Lopes; Tânia Melo; Felisa Rey; Joana Meneses; Fátima Liliana Monteiro; Luisa A. Helguero; Maria Helena Abreu; Ana Isabel Lillebø; Ricardo Calado; Maria Rosário Domingues (Molecules, 2020)
Marine edible macroalgae have functional proprieties that might improve human health and wellbeing. Lipids represent a minor fraction of macroalgae, yet with major interest as main carriers of omega 3 polyunsaturated fatty acids and intrinsic bioactive properties. In this study, we used lipid extracts from the green macroalgae Ulva rigida and Codium tomentosum; the red Gracilaria gracilis,Palmaria palmata and Porphyra dioica; and the brown Fucus vesiculosus, produced in a land-based integrated multitrophic aquaculture (IMTA) system. We determined the lipid quality indices based on their fatty acid profiles and their bioactivities as putative antioxidant, anti-inflammatory and antiproliferative agents. The results reveal to be species-specific, namely U. rigida displayed the lowest atherogenicity and thrombogenicity indices. Palmaria palmata and F. vesiculosus lipid extracts displayed the lowest inhibitory concentration in the free radical scavenging antioxidant assays. Ulva rigida, C. tomentosum, P. palmata and P. dioica inhibited COX-2 activity by up to 80%, while P. dioica and P. palmata extracts showed the highest cytotoxic potential in the MDA-MB-231 breast cancer cells. This work enhances the valorization of macroalgae as functional foods and promising ingredients for sustainable and healthy diets and fosters new applications of high-valued algal biomass, in a species-specific context.